Is Hospital Treatment in Australia Inequitable? Evidence from the HILDA Survey - Goodall, S; Scott, A (My University, 2008)
The pursuit of equity is a key objective of many health care systems, including Australia’s Medicare. Using the Household, Income and Labour Dynamics in Australia (HILDA) survey, we measured the extent of inequity in the utilisation of hospital services. We used methodology developed by the ECuity project for measuring horizontal inequity indices. We examine income-related health care inequities in both inpatient and day patient access and utilisation, whilst controlling for morbidity, demographic and socio-economic variables. The probability of hospital inpatient admission appeared equitable, but the probability of a day patient visit demonstrated a pro-rich distribution. Even more pronounced were the findings on the quantity of visits. The positive horizontal inequality indices indicate a degree of inequity favouring the rich, especially for inpatient utilisation. The pro-rich distribution of the probability of a day patient visit was associated with whether individuals held private health insurance. These results suggest that in Australia, which has a universal and comprehensive health system, the rich and poor are not treated equally according to need. Further research should investigate whether the causes of inequities lie in the preferences of individuals or the preferences of health care providers.
Melbourne Institute of Applied Economic and Social Research Working Paper Series
Keywords: Health -- Access to services; Health; Health and wellbeing; Income, wealth and finances; Health; Access to services; Health and wellbeing; Income, wealth and finances